Perceptions of two different alcohol use behaviours in pregnancy: an application of the prototype/willingness model - Tess Fletcher; Barbara Mullan; Amy Finlay-Jones (Health Psychology and Behavioral Medicine, 2022)
Objective: This study explored whether exposure to either an ‘ambiguous consumption’ prototype (no amount of alcohol specified) or a ‘small consumption’ prototype (‘small’ amount of alcohol specified) had an impact on prototype perceptions of, and willingness to use, small amounts of alcohol during pregnancy.Method: Participants were 140 women living in the UK, aged 20–45 years old, of whom 92% had previously been, or intended to become, pregnant. Participants completed measures to assess how favourably they viewed alcohol use in pregnancy, how similar they felt to those who would use alcohol in pregnancy and how responsible they perceived those who would use alcohol in pregnancy to be. Participant’s own willingness to use small amounts of alcohol during pregnancy was also assessed.Results: Having at least one child was positively correlated with being willing to accept an alcoholic drink while pregnant for those exposed to the ‘ambiguous consumption’ prototype only. Although perceptions of favourability, similarity and responsibility were consistently higher for those exposed to a ‘small consumption’ condition, there were no differences in willingness to drink according to exposure.Conclusion: This research suggests that women’s perceptions of those who drink alcohol while pregnant differ according to the amount of alcohol that they perceive as typical. This may have implications for how alcohol use in pregnancy is portrayed in public health messaging, particularly regarding the level of acceptance that may be associated with low to moderate alcohol use.